Electronics and Optical Properties of Nitrogen Doped Anatase for Solar Application - Nwankwo W. & Idiodi J. O. A., Olayinka A. S. (Covenant Journal of Physical and Life Sciences, 2019)
One of the major problems in developing countries is dearth of sufficient energy, which in turn hampers sustainable development. Anatase is one of the prominent polymorph of Titanium dioxide (TiO2) with great potential for solar application except for its wide band gap which limits its solar energy utilization to about 4%. It has fascinated much devotion from researchers owing to its extensive array of applications coupled with its availability and cost effectiveness. Doping has been presented as a means to narrow the band gap thereby enhancing its efficiency for solar application. Electronic and optical properties are presented here for pure and Nitrogen (N) doped anatase. The study is based on the density functional theory (DFT) using generalized gradient approximation (GGA) in addition to Coulomb Interaction (U) as implemented in quantum espresso code while the optical properties calculation was done with the Yambo code. With the inclusion of U parameter of 12.5eV, band gap of 3.1eV was obtained which compared favorably with experimental results. Doping concentration of 3.1% gave rise to band narrowing while Partial density of state (PDOS) shows that the band narrowing in anatase is due to the contribution from 2p state of the Nitrogen dopant. The optical properties calculated revealed that N-doped anatase has optical crests in the visible light range of electromagnetic spectrum which makes it a potential material for solar application with higher efficiency than pure anatase.